The Effect of Mindfulness-Based Intervention on Caregivers of Person with Chronic Schizophrenia (International Journal of Food and Nutritional Sciences, 2022)
When family members find out that a loved one has developed schizophrenia, they often feel helpless, angry, depressed, and anxious. As a result, the caregiver's psychological health is greatly affected, which increases both the caregiver's subjective and objective burden. As a result, they may require assistance and communication with mental health professionals at times. As a result, the study sought to assess the efficacy of mindfulness-based interventions on caregivers of people with chronic schizophrenia. Objectives: The study aimed to evaluate the effectiveness of a mindfulness-based intervention on various psychological parameters such as mindfulness, sense of control, and overall well-being in caregivers of people with chronic schizophrenia. Methodology: A total of 26 caregivers of persons with chronic schizophrenia, who fulfilled the inclusion and exclusion criteria were selected and formed into the Treatment As Usual (TAU) and Mindfulness Based Intervention with Treatment As Usual (MBITAU) groups. The current intervention was found to be effective in increasing well-being and mindfulness, particularly action awareness, as the MBITAU group differed significantly from the TAU group in the post-assessment. Thus, MBI can be an effective therapy to maintain the psychological health of caregivers